A Case of Milk Alkali Syndrome: The Forgotten Diagnosis of Generalized Weakness and Altered Consciousness - Hossain , Md Sabbir; Azad, Md Abul Kalam; Rahaman, Mohammad Ferdous Ur; Aftab, Kazi Ali; Rahman, Imrul Basher; Monira, Shirajum (Journal of Medicine, 2024)
This case reports outlines a 76-year-old male’s progression from papillary thyroid carcinoma diagnosis to the development of Calcium-Alkali Syndrome (CAS) following thyroidectomy. Initially presenting with thyroid mass, surgery was followed by generalized weakness and altered sensorium, investigations that revealed elevated calcium levels ,metabolic alkalosis and renal impairment . Diagnosis pointed to CAS, likely triggered by prescribed calcium and calcitriol post-surgery. Cessation of supplements and hydration resulted in resolution. While post-thyroidectomy hypocalcemia is anticipated, CAS poses challenges, especially with increasing calcium supplement use. This emphasizes the need for vigilant monitoring of electrolyte imbalances, particularly in regions with limited follow-up practices. Clinicians should balance preventing hypocalcemia without risking hypercalcemia, stressing the importance of timely identification and tailored interventions to prevent CAS complications. This case underscores the significance of recognizing CAS as a potential postoperative complication, urging vigilant monitoring and tailored management in similar clinical settings. J MEDICINE 2024; 25: 184-186